Niveles de comprensión lectora en estudiantes del quinto ciclo de educación primaria de la Institución Educativa Integrada César Góngora Perea Comunidad de Charupa Datem del Marañon 2022 - Curitima Sandoval, Regner (2024)
The objective of this study was to find the prevalent level of reading comprehension in which V Cycle of Primary Education of the integrated educational center that serves the community of Charupa learn. Since the study is of this nature, a quantitative research method is assumed, and the design is quite descriptive. Fifty V Cycle of Primary Education constituted the population; a sample of the same number was used for the census. The sampling was non-probabilistic. The instrument used was the questionnaire and the reading comprehension test methodology was applied. The tables containing the percentages and means of the data were examined by means of statistical graphs. The most relevant conclusions were the following: At the literal or beginning level of the reading process are the students of the V Cycle of Primary Education of the "César Góngora Perea" Integral Educational Institution of the Charupa Community, Datem del Marañón. We were able to address the specified objectives by using statistical tables and graphs to examine the data acquired and determine the mean, standard deviation and mode.